"A strange enough way": An embodied natural history of experience, animals and food on the Teslin Trail. (January 2015) - Peyton, Jonathan
Highlights: Animal bodies mediated the experience of nature in strange and precarious places. Animals were vital in pushing miners north, providing caloric and locomotive energy. The materiality of animals maintained the health and well-being of miners. The materiality of animals arbitrated the experience of the trail into terms more easily comprehended by miners. Abstract: This essay focuses on the use and abuse of animals and how the social and economic changes introduced by the gold rushers altered relationships between animals and humans in Northwest British Columbia and southern Yukon Territory during the haphazard scramble northward to the Klondike. I suggest that the embodied experience of life on the trail was articulated and mediated through the human–animal relationships forged out of necessity on the makeshift trails to the Klondike, built together by the boots of miners and the overburdened animals that moved goods through the northern plateaus. The animals brought into the Stikine performed two functions: vital roles of pack animals and, once their locomotive value was exhausted, as imported meat and by-products to be sold at market. I argue that the intimate and corporeal connections between humans and wildlife can mediate the experience of nature in unfamiliar and precarious places. In this sense, the very materiality of animals was essential for the maintenance of health and well-being and became the primary physical and emotional mechanism for rendering the extraordinary experience of the Teslin Trail into terms more easily rationalized and commodified by miners, merchants and local populations caught up in the epochal transformation brought into being in the closing years of the nineteenth century.